Optimising technical skills and physical loading in small-sided basketball games - Klusemann, M. J.; Pyne, D. B.; Foster, C.; Drinkwater, E. J. (Journal of Sports Sciences, 2012)
Differences in physiological, physical, and technical demands of small-sided basketball games related to the number of players, court size, and work-to-rest ratios are not well characterised. A controlled trial was conducted to compare the influence of number of players (2v2/4v4), court size (half/full court) and work-to-rest ratios (4x2.5 min/2x5 min) on the demands of small-sided games. Sixteen elite male and female junior players (aged 15-19 years) completed eight variations of a small-sided game in randomised order over a six-week period. Heart rate responses and rating of perceived exertion (RPE) were measured to assess the physiological load. Movement patterns and technical elements were assessed by video analysis. There were 60% more technical elements in 2v2 and 20% more in half court games. Heart rate (86 ± 4% & 83 ± 5% of maximum; mean ± SD) and RPE (8 ± 2 & 6 ± 2; scale 1-10) were moderately higher in 2v2 than 4v4 small-sided games, respectively. The 2v2 format elicited substantially more sprints (36 ±12%; mean ±90% confidence limits) and high intensity shuffling (75 ±17%) than 4v4. Full court games required substantially more jogging (9 ±6%) compared to half court games. Fewer players in small-sided basketball games substantially increases the technical, physiological and physical demands.